If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-4=-2(4-x)
We move all terms to the left:
3(x-4-(-2(4-x))=0
We add all the numbers together, and all the variables
3(x-4-(-2(-1x+4))=0
| –11u+8u+–2u+–15=–10 | | -44=4(1-3n) | | (7x+5)=47 | | 1-4v=-17 | | 0.2=z/528 | | 0.5+0.4=0.7x-0.4 | | 8=3/4a+13-a+4 | | 4m–2+6m=4 | | -57=3+4(1+4b) | | (6x-5)+(180-x)=180 | | (6x-5)+(175-6x)=180 | | -75y-35y=18+12 | | 4x-3=2x+24 | | 7/3x=10 | | (6x-5)+(6x-95)=180 | | 2=(7)(8)/a | | (6x-5)+(95-6x)=180 | | (6x-5)+(85-6x)=180 | | 1−5v+7=–6v+2 | | 4•x•12=32 | | 2x÷4=44 | | (x+30)+(2•x)+(x)=180 | | 3-4(-2x+3)=-41 | | 15y-(-12y)=50-12 | | 9+4p=-9 | | 2y-64=70 | | 5+b=10×7 | | 8+3x=5* | | X+30+2•x+x=180 | | x−10=−1 | | 5x+29=78 | | 20x-32=4x |